Effectiveness of polymyxin B hemoperfusion in acute exacerbation of interstitial pneumonia: a retrospective analysis: Polymyxin B and interstitial pneumonia - Lee, Song-I (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background Acute exacerbation (AE) of interstitial pneumonia (IP) occurs commonly and has a poor prognosis. Polymyxin B hemoperfusion (PMX-DHP) has a beneficial effect on AE of some types of IPs, particularly idiopathic pulmonary fibrosis (IPF). However, little is known about the efficacy of PMX-DHP in the Korean population. The aim of this study was to examine the effectiveness of PMX-DHP in AE of IP.MethodsWe conducted a retrospective study of 12 patients with AE of IP, including two patients with AE of IPF, who were treated with PMX-DHP at our center. Treatment with PMX-DHP was carried out once or twice. We collected and analyzed data on changes in oxygenation with PMX-DHP and survival after AE.ResultsIn patients with AE of IP, the ratio of partial pressure of arterial oxygen to the fraction of inspired oxygen, or the P/F ratio, had significantly improved at the end of the treatment with PMX-DHP (87.0 [80.3–130.9] to 200.6 [105.0–245.5] mmHg, p = 0.019). The white blood cell (WBC) count had significantly reduced at the end of the treatment (12,400 [8,860–20,287] to 6,800 [3,950–15,775]/mm3, p = 0.050). The 28-day and in-hospital mortality rates of patients after AE of IP were 41.7 % and 75.0 %, respectively.ConclusionsPMX-DHP improved oxygenation and reduced the WBC count in patients with AE, with either steroids aloneor steroids and cyclophosphamide. Further studies are required to verify the potential benefits of PMX-DHPfor patients with AE of IP.